Thermal Comfort Evaluation of Baitul Makmur Mosque in Kapuas Coastal Area: Field Measurement and CFD Simulation Approach - Ari Fitriyanto; Rissa Fitria Syafutri; Indrayadi (Program Studi Arsitektur, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2026)
This study evaluates the thermal comfort performance of Baitul Makmur Mosque located in the coastal area of the Kapuas River, Pontianak. The research aims to identify the factors influencing indoor thermal discomfort and to propose passive design improvement strategies. Field measurements were conducted using thermohygrometers and anemometers at six interior and exterior observation points for 30 days during five daily prayer periods. Computational Fluid Dynamics (CFD) simulation was performed to analyze airflow behavior under different environmental conditions. The results indicate that indoor temperature frequently exceeds thermal comfort limits, particularly during afternoon prayer periods, while relative humidity remains consistently high throughout daily cycles. Airflow analysis shows that the existing ventilation system is unable to distribute airflow effectively, resulting in stagnant airflow zones and uneven thermal distribution. CFD simulation confirms that the mosque building configuration restricts airflow penetration despite strong external wind potential. The study recommends passive design improvements including cross ventilation optimization, enhancement of upper ventilation openings, and addition of shading elements to improve thermal performance. The findings contribute to passive thermal design knowledge for mosque buildings located in humid tropical coastal environments. Keywords: thermal comfort, mosque building, passive design, natural ventilation, CFD simulation